CRITERIA FOR MONITORING OF GAS WELLS IN THE PERIOD OF DECLINING PRODUCTION - Raisa E. Shesterikova (Вестник Северо-Кавказского федерального университета)
The article presents the monitoring of the wells in the period of falling production, using the energy cri- terion will ensure reliable operation conditions marginal wells and the planned level of gas.